PENERAPAN MODEL DISCOVERY LEARNING DAN DAMPAKNYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 4 PADANG - Ditha Rahayu (Jurnal Edukasi dan Penelitian Matematika, 2021)
Problem solving ability is ability of students to be able to solve problem using a clear and systematic process to get the right answer. The reality in the field is that the mathematic problem solving of students in the class XI MIPA SMA Negeri 4 Padang is still low. One of the efforts made is by applying the Discovery Learning model in the mathematics learning proccess. The purpose of this study was to determine the impact of the application of the Discovery Learning model on the mathematical problem solving abilities of students in class XI MIPA SMA Negeri 4 Padang. This study uses a quantitative descriptive approach and this type of research is pre-experimental (pre-experimental) with a one shot case study design. The class determination of the research subjects was carried out using a purposive sampling technique based on the considerations of the mathematics teacher class XI MIPA SMA Negeri 4 Padang, the chosen one was class XI MIPA 3. The results showed that the mathematical problem solving ability of students in class XI MIPA SMA Negeri 4 Padang with the application of the Discovery Learning model in learning has increased. Keywords–Matematical Problem Solving, Discovery Learning Model, Pre-Experiment